Outdoor environment modeling using BSP techniques - Pek, Vincent. (2009)
This Final year project seeks to explore a new avenue for the increasing focus on the gaming industry, to explore the possibility of having Binary Space Partitioning (BSP) tree applied to all possible objects in the outdoor environment scene. This project attempts to combine the indoor environment and outdoor environment together in order to eliminate the required loading time in between game play. This simulation is developed using C++ on Microsoft Visual Basic C++ program with DirectX library installed. Another main program is 3D Studio Max 9 from Autodesk®, which is used to create the 3D models required for this project. The objects created are translated to XML documents to be read by C++ in order to processed it into BSP trees and traverse the tree during runtime and render the scene. It aims to reduce the loading time and increase frame rate. The required results was obtained y running the simulation multiple times each with different number of polygons rendered into the scene. Results were then compared with expected theoretical results and it has proved to be quite infeasible to be used on an extensive large scale outdoor environment. However with the usage of BSP on models, it can greatly enhance the realistism of objects as collision detection to the objects are made more precise as it is comparing with the polygons of the models instead of a bounding box of the model. Finally, there are much more applications that can be utilized with the BSP tree, in order to further improve rendering time. The developer also hopes to present this report as one of the milestone to start of this for more research based on BSP trees.